Sensitivity of microorganisms associated with biofilm of root canals to antimicrobic medicines (LLC "Endo Press", 2020)
Conducted a survey of the contents of the root canal and periapical lesions in 38 patients with clinical diagnosis of chronic pulpitis and chronic apical periodontitis (17 and 21 respectively), aged from 17 to 72 years. It was found that microbiocenoses in root canals have different composition in pulpitis and periodontitis, biofilms are associations of facultative and obligate anaerobes of 2 or 3 types. The efficiency of the use of irrigants 3% solution of sodium hypochlorite and 0.5% chlorhexidine solution was studied. Less activity was detected in 0.5% solution of chlorhexidine against obligate anaerobes allocated for chronic periodontitis.